Implementação de suporte à alta disponibilidade em ambientes NFV usando OSM - Saito, Alexis Seiki (2018)
High Availability is the most important aspect when discussing resiliency over telecommunications systems in the context of the adoption of the cloud computing paradigm, a big challenge for telecommunications service providers. Initiatives of NFV platform implementations like OpenMANO (strongly based on NFV standardization from ETSI) serve as base to run experiments like the one proposed in this master project, in which we describe our contribution to an implementation of management for high availability on top of platform proposed by Open Source MANO (OSM). The high availability implementation presented in this project is adherent to ETSI standardization and contributes to one of the most important NFV frameworks that up to now has not presented support to such feature. In this project, we present an experimentation over OSM implementation which involves the whole environment with its technological complexity. In concrete terms, our contribution addresses two main aspects: a proposal for information modeling based on ETSI standardization on high availability and its implementation in the OSM framework. Such implementation consists in the detection of failure by the orchestrator implying in a network reconfiguration as a mechanism to support redundancy in an active-active scenario. The experiment was tested and evaluated in a real minimalist environment to demonstrate the implementation performed to manage high availability information and re-orchestrate data flows between redundant VNFs.